Relationship between offensive modalities and results in elite basketball games - Selmanovic, A.; Jelicic, M.; Dizdar, D. (SportMont, 2023)
Basketball is characterized by a set of alternating offensive and defensive phases generally limited by the change in ball possession, also known as conversion. The aim of this research was to evaluate the difference in offensive types between the winning and losing, noting the variance in game result. A sample composed of 2607 entities representing basketball offense was collected by random selection of 15 Euroleague playoff games. The collected data were processed by the Match Analysis System, and the offense was classified into three basic types: set, transition, and early offense. With nearly equal opponents there is evident a high dynamic balance of transitions, set offenses, as well as other forms of offense, therefore the initial results showed no statistical difference in the distribution and success of offensive forms between opponents in balanced matches. There is significant change evident when focusing on the game periods with the highest point differential. In these periods the winning teams showed above 20% more fast breaks, which is proved to be the most effective type of offense, in addition to significantly better 2-point and 3-point shooting efficiency during set plays. Even though the losing team in balanced matches successfully controlled most of the game, and perhaps even outplayed the opponent, the identified critical intervals ("scoring runs") proved to be a decisive factor in the final outcome of the game.